Changing patient profile, hearing aid use and disability among first-time hearing aid users in Singapore over a decade - Ho, Eu Chin (2021)
Objectives: To examine the time trends in demographics, hearing characteristics, hearing aid (HA) choices, usage and patient-reported disability among first-time HA users in Singapore over a decade. Design: Cross-sectional study. Study sample: 1052 subjects issued with HAs at a tertiary hospital from 2004 to 2013. Results: An increase in number of first time HA users were seen from 2004 to 2013. Although mean age did not change significantly, the proportion of older adults (>80 years) being fitted increased (p for trend ¼ 0.033). Inflation adjusted cost of HAs rose over time (p < 0.001 for trend). Bilateral HA uptake increased (adjusted odds ratio [AOR] ¼ 1.58 (95% Confidence Interval [CI] 1.35–1.85) while use of customisable HAs decreased (AOR ¼ 0.74, 95% CI 0.66–0.84) over the period. A decrease in the proportion of subjects reporting 5 or more disabilities (AOR ¼ 0.45, 95% CI 0.34–0.59) and using their HAs >7 hours daily (AOR ¼ 0.45, 95% CI 0.34–0.59) was seen. Conclusion: From 2004 to 2013, there was a positive trend towards HA uptake in Singapore. Bilateral HA uptake increased while customisable in ear type of HA use decreased. While hearing disability showed a decreasing trend, HA usage remained suboptimal. Abbreviations: BTE: Behind the ear; CIC: Completely in the canal; HAE: Hearing aid evaluation; HAF: Hearing aid fitting; ITC: In the canal; ITE: In the ear; PHAF: Post hearing aid fitting; RIC: Receiver in canal